Overnutrition in Indian Children: Challenges and Opportunities - Prema Ramachandran; K. Kalaivani (Frontiers Media S.A., 2022)
Global and Indian data indicate that children from all the segments of population face dual nutrition burden and related health consequences. Long-term cohort studies have shown that both the under- and overnutrition are risk factors for overnutrition and non-communicable diseases in adult life. Halting the rise in overnutrition is one of the Sustainable Development Goal (SDG) targets to be achieved by 2030. With the development and inclusion of body mass index (BMI)-for-age in the WHO child growth standards, it has become possible to assess over- and undernutrition in short-statured children. In India, the Annual Health Survey (AHS) (2014) and the District Level Household Survey 4 (DLHS4) (2013) undertook measurement of height/length and weight (AHS 557016 and DLHS4 295663) in the 0-18-year of school-age children from selected households. Prevalence of overnutrition in 0-18-year children was calculated from these two surveys by using the WHO standards for BMI-for-age (BMI-for-age z scores (BAZ) > +2 in 0-5 and BAZ > +1 in 5-18-year children) as well as uniform norms of either > +1 or > +2 BAZ across 0-18-year children. An attempt was made to explore the policy and program implications of using different norms for assessing overnutrition in preschool and school age children in the Indian context. Body mass index-for-age curve for the 0-18-year Indian children was calculated and compared with the WHO BMI-for-age curve. Across 0-18-year children, the mean BMI-for-age of Indian boys and girls was lower than the mean of the WHO standards, but the trajectory followed was similar. Therefore, Indian high-risk under- and overnourished children can be monitored by using the WHO BMI-for-age curve. Irrespective of the cutoff used for BMI-for-age, prevalence of overnutrition was higher in preschool as compared to school-age children. Overnourished school-age children outnumbered preschool children, especially if the WHO cutoffs were used. The school health system may find it difficult to implement programs that aimed at detection and management of large number of overnourished children. If uniform norm of BAZ > +1 was used, prevalence of overnutrition in preschool children was high and almost similar to undernutrition. Currently, nutrition programs for preschool children are focused on undernutrition and they may find it difficult to manage program focused on overnutrition in large number of children. If the uniform norm of BAZ > +2 was used, both the prevalence of overnutrition and number of children requiring intervention were relatively low in all the age groups. The existing preschool and school nutrition programs can take up an integrated program aimed at early detection and effective management of both the under- (BAZ < −2) and overnutrition (BAZ > +2) in 0-18-year children and strive to achieve the SDG targets.